One-Pot Reductive Allylation of Amides by Using a Combination of Titanium Hydride and an Allylzinc Reagent: Application to a Total Synthesis of (–)-Castoramine - Itabashi, Suguru; Shimomura, Masashi; Sato, Manabu; Azuma, Hiroki; Okano, Kentaro; Sakata, Juri; Tokuyama, Hidetoshi (Synlett, 2018)
A one-pot direct reductive allylation protocol has been developed for the synthesis of secondary amines by using titanium hydride and an allylzinc reagent. This protocol is applicable to a broad range of substrates, including acyclic amides, benzamides, α,β-unsaturated amides, and lactams. The stereochemical outcome obtained from the reaction with crotylzinc reagent suggested that the allylation reaction proceeds through a six-membered cyclic transition state. A total synthesis of (–)-castoramine was accomplished by following this protocol for the highly stereoselective construction of contiguous stereocenters.
Keywords: amides; reduction; allylation; amines; total synthesis; alkaloids